Analysis of Fractional Bioconvection with Hybrid Nanoparticles in Channel Flow. (23rd August 2022) - Asjad, Muhammad Imran; Ikram, Muhammad Danish; Sarwar, Noman; Muhammad, Taseer; Sivasankaran, Sivanadam; Subaihi, Sami Ahmed Abdu
Abstract : In this paper, MHD Brinkman-type fluid flow containing titanium dioxide and silver nanoparticle hybrid nanoparticles with generalized Mittag–Leffler kernel-based fractional derivative is investigated in the presence of bioconvection. The governing equations with dimensional analysis and fractional approach are obtained by using the fractional Fourier's law for heat flux and Fick's law for diffusion. As a result, the bioconvection Rayleigh number, which is responsible for the declining in the fluid velocity and fractional parameters used to control the thermal and momentum boundary layers thickness of fluid properties. The obtained solutions can be beneficial for proper analysis of real data and provide a tool for testing possible approximate solutions where needed.